POVERTY REDUCTION MEASURES IN THE CONTEXT OF SOCIAL WORK WITH FAMILIES - Gorskytė, Karolina; Povilaitienė, Neringa (PROFESSIONAL STUDIES: Theory And Practice, 2022)
The problem of poverty is one of the biggest and most difficult to solve worldwide. Every fifth person in Lithuania experiences poverty. The aim of the article is to reveal the poverty reduction measures in the context of social work with families. The study involved 6 informants: 4 social workers and 2 case managers. The results of the study revealed that most often families experienced poverty due to: alcohol dependence, lack of social skills, and lack of motivation. Individuals experience financial difficulties, their physiological needs are not met. There are conflicts between family members, children are not taken care of. The study has found that reducing family poverty, social workers use the following assistance measures: provision of social services, family involvement in social life, and financial, emotional and material assistance. Providing help, they encounter: clients’ reluctance to accept assistance, lack of motivation to work and change, and psychological problems of families. Keywords: poverty, social work, social services, social assistance, social insurance.